Accent, Language, and Race: 4–6‐Year‐Old Children's Inferences Differ by Speaker Cue. Issue 5 (5th April 2017) - Weatherhead, Drew; Friedman, Ori; White, Katherine S.
Abstract : Three experiments examined 4‐ to 6‐year‐olds' use of potential cues to geographic background. In Experiment 1 ( N  = 72), 4‐ to 5‐year‐olds used a speaker's foreign accent to infer that they currently live far away, but 6‐year‐olds did not. In Experiment 2 ( N  = 72), children at all ages used accent to infer where a speaker was born. In both experiments, race played some role in children's geographic inferences. Finally, in Experiment 3 ( N  = 48), 6‐year‐olds used language to infer both where a speaker was born and where they currently live. These findings reveal critical differences across development in the ways that speaker characteristics are used as inferential cues to a speaker's geographic location and history.